Wicked autumn eaudiobook A max tudor novel. - Malliet, G. M. (Max Tudor., 2011)
Max Tudor has adapted well to his post as vicar of St. Edwold's in the idyllic village of Nether Monkslip. The quiet village seems the perfect home for Max, who has fled a harrowing past as an MI5 agent. But this new-found serenity is quickly shattered when the highly vocal and unpopular president of the Women's Institute turns up dead at the Harvest Fayre. The death looks like an accident, but Max's training as a former agent kicks in, and before long he suspects foul play. As the investigation unfolds, Max becomes more intricately involved. Memories he'd rather not revisit are stirred, evoking the demons from the past which led him to Nether Monkslip.